The Influence of Socioeconomic Status and General Health on the Fracture Incidence - Atia, Yasir A; Al-Attar, Zaid; Naji, Raghad E (Scripta Medica, 2023)
Background/Aim: There is an association between patient general health, socioeconomic status and fracture incidence. Aim of this study was to demonstrate the relation between the socioeconomic and health status and the occurrence of fractures in Al-Kindy Hospital residents. Methods: A prospective cross-sectional study was performed by using data collected from fractured patients in Al-Kindy Teaching Hospital / Baghdad orthopaedics outpatient clinic, between 12 December 2021 and 8 March 2022. A 100 patients aged 20 to 75 years were included in this study. The data were collected using a researcher-administered questionnaire, which included items to assess patient’s socioeconomic status (accommodations, occupation, income status, level of education, owing motor vehicle) and assessed patient’s health status (height, weight, presence of chronic disease(s), smoking status, alcohol consumption, water source quality, sun exposure, nutrition status). Results: A 100 patients from Al-Kindy Teaching Hospital between the age 20-75 participated in the study. The incidence of fractures was higher in younger and more active males (68 %) than females (32 %). Highest percent appeared in lower group of socioeconomic status (58 %) and in lower group of health status (44 %). There was a significant relation between health status and body mass index (BMI). Obese and overweight patient were the more vulnerable to fractures. Conclusion: Fractures are more likely to happen to people with low socioeconomic status, low general health status and overweight people.